Kebijakan Elijah Muhammad pada Gerakan Nation of Islam (NoI) dalam Memperjuangkan Etnis Afro-Amerika di Amerika Serikat - Sidik Fauji (Department of Political Science - Universitas Sains Al-Qur’an, 2019)
The US people had discriminated Afro-Americans in various spheres. In the midst of the discrimination as well as the racism experienced by the blacks, a mysterious merchant called Fard emerged in 1930. As a form of existence and resistance toward the wide-spread discrimination and racism as well as to raise the voice of the citizens who did not get their rights and justice, he founded the Nation of Islam (NOI). One of Fard's disciples, Elijah Muhammad, then led and developed NOI in 1934-1975. The purpose of this research is to explain Elijah Muhammad's struggle in dignifying the Afro-American ethnic and his influence in the NOI movement. Focusing on literary research, the method used in this research is historical analysis, while the activities carried out in the analysis include topic selection, heuristics, criticism, interpretation and historiography. The results obtained from this research are descriptions of Elijah Muhammad's policies in uplifting the identity of the Afro-American ethnic. In this case, Elijah Muhammad at least took two measures in the movement that he led, namely recovering the Black identity to be respectfully recognized and developing economic independence.